Waste of drying coffee beans as a substrate alternative in coffee conilon seedlings - Meneghelli, Caroline Merlo; Lo Monaco, Paola Alfonsa Vieira; Haddade, Ismail Ramalho; Meneghelli, Lorena Aparecida Merlo; Krause, Marcelo Rodrigo (Coffee Science - ISSN 1984-3909, 2016)
Among the various wastes generated during the coffee in the mountainous region of the Espiríto Santo state, “moinha” stands out from graim during. Because of their nutritional potential and the need have properly in the environment, it is aimed, with this work, evaluate the use of the different concentrations of the moinha as alternative substrate for vegetative development Conilon coffee seedlings. Was used a randomized block design, with four replicates, with split plot in the time. Different substrates were allocated in the plot (T1: soil + cattle manure at a ratio of 3: 1; T2: 10% moinha + soil; T3: 20% moinha + soil, T4: 30% moinha + soil and T5: 40% moinha + soil) and, in the subplots, the different ages of evaluation (60, 82, 104 and 126 days after planting). Variables such as changes in height, stem diameter, crown diameter, number of leaves and fresh and dry matter of root and shoot were submitted to ANOVA, F test hair, and as media, compared hair test Dunnet (α = 0.05). The use of the conventional substrate can be replaced hair by the substrate containing 10% moinha without there be difference in plant height as well as in dry and fresh matter shoot, what demonstrates it potential use as for the alternative substrate for producing seedlings.